Syariah Courts criminal jurisdiction Amendment Bill 2016: From the constitutional perspective - Mokhtar, Khairil Azmin (2017)
The proposal to amend ACT 355, namely the Syariah Courts Criminal Jurisdiction Act, in 2016-2017 has received various reactions from the public. The mixed reactions are caused by various factors. For most people the proposal is timely and necessary but on the other hand there are some people who oppose it. It is viewed that the opposition to the proposed amendment is caused mainly to the misunderstanding of many aspects relating to the law, constitution and power of the government. The talk is to deal with the matters and clarify the issues so that it can be objectively assesed before coming to any conclusion.